A System Dynamics Model for Environmental Quality and Urban Quality of Life through Smart City Implementation - Rifky Roudana Imani Cahya; Erma Suryani (TIN: Terapan Informatika Nusantara, 2026)
Smart city programs are increasingly adopted to enhance urban environmental performance through digital innovation and sustainable governance; however, solid waste accumulation and carbon dioxide (CO₂) emissions remain persistent challenges in rapidly expanding cities. This study evaluates the environmental impacts of smart city implementation in Surabaya by quantitatively examining waste stock dynamics and CO₂ emission behavior using a system dynamics approach. The analysis focuses on the environmental subsystem, particularly smart waste management and air emission control, which are modeled through a Causal Loop Diagram (CLD) and a Stock and Flow Diagram (SFD) to capture feedback mechanisms between waste generation, waste processing, stock accumulation, and emission growth. Simulation results for the 2020–2024 period show that the implementation scenario performs significantly better than the base model, achieving an average reduction of approximately 6–7% in waste stock and about 5% lower CO₂ emission levels by the end of the simulation horizon. These improvements are primarily driven by increased waste processing efficiency, which directly suppresses waste accumulation and indirectly slows emission growth. Nevertheless, the magnitude of environmental benefits is strongly influenced by technological readiness and the operational capacity of the environmental management system. Overall, the findings provide quantitative evidence that integrating waste management and emission control within smart city frameworks is essential for achieving measurable and sustainable improvements in urban environmental quality.